Effects of fermented wheat bran on growth performance, nutrient digestibility and intestinal microbiota of weaned piglets - Jia, Ninghui; Jin, Jin; Wei, Xinru; Trabalza-Marinucci, Massimo; Jia, Gang; Zhou, Qiang; Zhang, Ruinan; Li, Hua; Wu, Fali; Zhao, Hua; Luo, Hefeng; Che, Lianqiang; et al. (Frontiers in Veterinary Science, 2025)
The objective of this study was to investigate the effects of fermented wheat bran (FWB) on growth performance, nutrient digestibility, serum biochemistry, short-chain fatty acids, and intestinal microbiota of weaned piglets. One hundred twenty-eight weaned piglets were randomly assigned to 4 groups, each with 8 pens and 4 piglets per pen: basal diet group (BD), 5% wheat bran group (5% WB), 5% fermented wheat bran group (5% FWB), and 10% fermented wheat bran group (10% FWB) for a 28-day trial. Results showed that compared to the BD group, the diarrhea rate in the 5% WB group was significantly increased (p < 0.05) at d 15–28 and d 1–28. In contrast, at d 15–28 and d 1–28, the diarrhea rates in the 5% FWB and 10% FWB groups were significantly lower than those in the 5% WB group and showed no significant difference compared to the BD group. Moreover, the apparent total tract digestibility (ATTD) of DM, GE, CP, EE, CF and ADF at d 1–14, and EE and NDF at d 15–28 in the 5% FWB group were significantly improved compared to the 5% WB group (p < 0.05). However, only the ATTD of CP, EE and CF at d 1–14 in the 10% FWB group were significantly higher than those in the 5% WB group (p < 0.01). Compared to the BD group, the pH of cecum chyme and serum urea nitrogen content in the 5% FWB and 10% FWB groups were significantly reduced (p < 0.05), and those in the 10% FWB group were significantly lower than those in the 5% WB group (p < 0.01). The propionic acid content of cecum chyme in the 5% FWB and 10% FWB groups, and butyric acid content in the 10% FWB group were significantly higher than those in the BD group (p < 0.05). LEfSe analysis (LDA score > 3.0) identified 4 species, 6 species of Proteobacteria, 2 species, and 9 species that were enriched in the BD, 5% WB, 5%F WB and 10%F WB groups, respectively. Additionally, Dialister, Prevotellaceae_NK3B31_group, Mitsuokella, Succinivibrio, and Prevotella were significantly and positively correlated with the concentrations of valeric acid, propionic acid, and acetic acid (p < 0.05). In conclusion, 10% FWB supplementation in weaned piglet diets did not affect growth performance, it reduced the diarrhea rate compared to the 5% WB group, potentially due to enhanced nutrient digestibility, elevated SCFAs levels, and shifts in microbial composition.